Productivity and profitability of Indian mustard (Brassica juncea L.) as influenced by soil solarization and weed management practices (Journal of Oilseed Brassica, 2026)
A field experiment was conducted at Dr. BSKKV, Dapoli, Maharashtra during 2020-21 (rabi season) to find out the efficient weed control measure through soil solarization in Indian mustard (Brassica juncea L.). The results revealed that significantly maximum growths, yield parameters, plant height (175 cm), number of branches plant-1 (5.2), number of siliquae plant-1 (161), siliquae weight plant-1 (9.34 g), siliquae length (4.36 cm), number of seeds siliquae -1 (12.85), seed weight plant-1 (10.36 g), test weight (2.81 g), seed yield (11.14 q ha-1), stover yield (26.47 q ha-1) and harvest index (25.58 %) were noticed under soil solarization treatment along with transparent polythene except weed count and weed dry matter which was significantly low in soil solarization with black polythene. The maximum values of most of growth and yield parameters and weed control efficiency were recorded in weed free check followed by pre-emergence application of oxadiargyl 80% WP @ 100 g ha-1, post-emergence application of quizalofop-ethyl 10 % EC @ 45 g ha-1, and weedy check. Though, weed free check without soil solarization was found the most profitable.